Sympathetic nervous system activation, arterial shear rate, and flow-mediated dilation - Thijssen, D.; Atkinson, C.; Ono, K.; Sprung, V.; Spence, Angela; Pugh, C.; Green, D. (The American Physiological Society, 2014)
The aim of this study was to examine the contribution of arterial shear to changes in flow-mediated dilation (FMD) during sympathetic nervous system (SNS) activation in healthy humans. Ten healthy men reported to our laboratory four times. Bilateral FMD, shear rate (SR), and catecholamines were examined before/after 10-min of −35-mmHg lower body negative pressure (LBNP10). On day 1, localized forearm heating (LBNP10+heat) was applied in one limb to abolish the increase in retrograde SR associated with LBNP. Day 2 involved unilateral cuff inflation to 75 mmHg around one limb to exaggerate the LBNP-induced increase retrograde SR (LBNP10+cuff). Tests were repeated on days 3 and 4, using 30-min interventions (i.e., LBNP30+heat and LBNP30+cuff). LBNP10 significantly increased epinephrine levels and retrograde SR and decreased FMD (all P < 0.05). LBNP10+heat prevented the increase in retrograde SR, whereas LBNP10+cuff further increased retrograde SR (P < 0.05). Heating prevented the decrease in percent FMD (FMD%) after LBNP10 (interaction effect, P < 0.05), whereas cuffing did not significantly exaggerate the decrease in FMD% (interaction effect, P > 0.05). Prolongation of the LBNP stimulus for 30-min normalized retrograde SR, catecholamine levels, and FMD (all P > 0.05). Attenuation of retrograde SR during 30 min (LBNP30+heat) was associated with increased FMD% (interaction effects, P < 0.05), whereas increased retrograde SR (LBNP30+cuff) diminished FMD% (interaction effects, P < 0.05). These data suggest that LBNP-induced SNS stimulation decreases FMD, at least in part due to the impact of LBNP on arterial shear stress. Prolonged LBNP stimulation was not associated with changes in SR or FMD%. Our data support a role for changes in SR to the impact of SNS stimulation on FMD.